An Overview of Treatment Guidelines and Methods of Synthesis of Drugs Used in Leprosy Chemotherapy - Pinheiro, Luiz C.S.; Borges, Julio C.; Campos, Vinicius R.; Dantas, Leonardo C. (Mini Reviews in Medicinal Chemistry, 2023)
Leprosy is a Neglected Tropical Disease (NTDs) caused by Mycobacterium leprae (M. leprae). The treatment is considered effective, however, the high dose Multidrug Therapy (MDT) for a long period and its adverse effects result in the abandonment of the treatment by patients. Indeed, antimicrobial resistance is still an obstacle that must be overcome in the treatment of leprosy. In the present article, we reviewed the WHO guidelines for the chemotherapy of leprosy and the methods of synthesis of these drugs.
Keywords: Leprosy